Assessing the suitability of rooftop solar photovoltaic systems for sustainable electricity generation - Aldhshan, Shaban R. S.; Khairul Nizam Abdul Maulud; Karim, Othman A.; Wan Shafrina Wan Mohd Jaafar; Mohd Faizal Fauzan (Penerbit Universiti Kebangsaan Malaysia, 2023)
The adoption of solar energy as a sustainable solution is gaining momentum in Malaysia. Universities, as prominent stakeholders, are at the forefront of implementing energy efficiency and renewable generation objectives. This study aimed to evaluate the suitability of photovoltaic systems for electricity generation by assessing the solar radiation potential of the Universiti Kebangsaan Malaysia (UKM) campus in Bangi. Geospatial data and GIS approaches were utilized to characterize solar potential across the 1096-hectare campus. Unmanned aerial vehicle (UAV) images were processed to derive digital surface models, enabling the calculation of slope and aspect. By considering slope, aspect, shadow, area, and total solar radiation, suitable buildings for photovoltaic installation were identified. Out of the 546 buildings assessed, two were highly suitable, seven were suitable, 32 were moderately suitable, 134 were unsuitable, and 367 were highly unsuitable. The selected rooftops have the potential to generate 69,975 MWh annually, representing about 17% of the total electricity consumption from the grid. These findings highlight the viability of rooftop solar arrays for UKM and suggest an estimated energy production ranging from 9,949 MWh/year. The methods employed in this study, leveraging high-resolution UAV images, can be adapted to comprehensively assess solar potential in other institutions across Malaysia, contributing towards meeting campus energy goals and advancing sustainable practices.